Activities of HMR 3787 and RU 64399 Compared with Those of Four Other Agents against Haemophilus influenzae and Haemophilus parainfluenzae - Bozdogan, Bülent (American Society for Microbiology, 2003)
Activities of HMR 3787, a new 2-fluoroketolide, and its (des)-fluor derivative, RU 64399, were tested against 111 Haemophilus influenzae and 26 H. parainfluenzae strains and compared with those of telithromycin, erythromycin, azithromycin, and clarithromycin. HMR 3787 and RU 64399 MICs were comparable with those of azithromycin but were less affected by incubation in CO(2). Time-kill studies of 12 strains showed that HMR 3787, RU 64399, and telithromycin were bactericidal against all strains after 24 h at two times the MIC.